An investigation on the behavior of anisothermal adhesive contact based on Maugis–Dugdale model. (August 2019) - Zhu, Xinyao; Wang, Fujun; Zhang, Dawei
Abstract: The present study considers the effect of heat conduction on the behavior of adhesive contact between two elastic spheres of different temperatures, where the adhesion forces are supposed to follow the Dugdale model. The thermal adhesive contact issue is transformed into two intercoupled nonlinear integral equations which are governed by two parameters: λ (adhesion parameter) and M . By means of iteration method, numeric results are obtained. Analogous to the traditional Maugis-Dugdale (M-D) model, the results provide transition of the pull-off force between JKR and DMT type contact models through the adjustment of the adhesion parameter λ with fixed parameter M . On the other hand, with a fixed adhesion parameter λ, it is indicated that the shape of the force-contact radius curve and the pull-off force are dependent on the parameter M . Finally, we find the uniformity of the pressure distribution is affected by the applied load F and adhesion parameter λ .